(untitled) (Intent Research Scientific Journal, 2023)
The article covers the modern requirements for the safety of urban ecology and aspects of their separation into ecological zones. Also, the main tasks of modern urban planning are the construction of cities and towns with an individual appearance, the solution of urban environmental issues, the preservation of old urban centers and repairs on a scientific basis.